Synthesis of functionalized carboxyalumoxanes as the fillers of polymeric nanocomposites - Affek, M.; Dębowski, M.; Florjańczyk, Z. (Polimery, 2022)
The reactions of boehmite with carboxylic acids or andydrides [see Table I and equation (1)] have been used for the synthesis of alumoxanes containing various functional groups. The courses of the reactions (with acrylic, metacrylic or lactic acids and maleic or succinic anhydrides) were monitored using FT-IR (Figs. 1, 5-7) and C-13 NMR (Fig. 2) methods. The reactions of boehmite with metacrylic acid lead to carboxyalumoxanes (KAO) which can be used as reactive fillers in radical copolymerization reactions. Acryloalumoxane modified with lauric acid radicals (amounts 30-80%) was polymerized with styrene and lipophylic fillers able to further copolymerization with vinyl monomers have been obtained. Products of the reaction of boehmite with lactic acid are nanoparticles of size up to 200 nm (Fig. 3 and 4). Particle size and particle size distribution can be controlled by the reaction conditions. KAOs obtained from boehmite and maleic or succinic anhydrides contain free carboxylic groups which can be active in polycondensation processes.